PERANAN PEMBERDAYAAN MASYARAKAT DALAM PENINGKATAN MUTU PEMBANGUNAN - NURKARIM NEHE (LP2MTBM MAKARIOZ, 2020)
This paper aims to determine the existence of community empowerment in improving development, through library research methods. From the discussion it can be concluded that community empowerment in improving development can provide direction in achieving the goals and objectives of community development in an optimal and sustainable manner. Directed is clearly used as a basis for controlling and evaluating the level of success.